Practical Steps in Designing Intervention to Increase Childbearing Desires: An Intervention Mapping Approach - Fatemeh Darabi; Sevil Momeni Shabani; Afrouz Mardi; Nazila Nejhaddadgar (Gonabad University of Medical Sciences, 2023)
Background: Increasing the desire to have children is an important priority of the healthcare systems, which requires targeted planning. This paper describes the development of an intervention program using an intervention mapping approach (IMA) to increase the childbearing desires. Methods: From July to November 2022, the steps of the IMA process were completed. Starting with needs assessment, in this stage, we conducted a literature review, created focus groups, and conducted interviews with local stakeholders; meanwhile, the program objectives and the target audience were determined. Then, the road map for targeted interventions was prepared. Results: The needs assessment completed questionnaires (n=1288), the literature review, 3 focus groups (n=25 participants), in addition to interviews (n=30 participants) indicated that the most effective factors in the parents' childbearing low desires were concern about the future of their children, economic problems, low parenting skills, and low skills to interact with their spouse. According to the PRECEDE-PROCEED model awareness, attitude, and self-efficacy were categorized as determinants at the individual level, perceived subjective norm at the family level, and organizational changes at the social level based on the results of the needs assessment. The findings from each step of the process informed successive steps. Conclusion: The IMA is a control-oriented, systematic, participation-based technique to design and implement targeted and ongoing health promotion programs.